PENGEMBANGAN MODEL SELF DIRECTED LEARNING MELALUI DARING BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN MENGENAL SIMBOL ANGKA DAN BILANGAN PADA ANAK USIA DINI - Chandra Asri Windarsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to find out how the Self Directed Learning model through android-based online to improve the ability to recognize number symbols and bilagan in early childhood. In this study using descriptive method with qualitative approach by analyzing selft directed learning seen from the ability to recognize numbers and numbers in children.  The population of this study is 8 children of group A with an age range of 4-5 years in TK Bandung Barat Foundation Cipatat District School Year 2020-2021. The results of this study show that the scenario using the Daily Learning Implementation Plan and implemented with android through online, as for the impact for learners by using the Model Self Directed Learning children develop their abilities from BB (Undeveloped) turned into BSH ( Developing As Expected).